CHALLENGING THE RULES OF INFLUENCER MARKETING: EMERGING SENSITIVITIES AROUND CHILDREN’S PRESENCE IN FAMILY INFLUENCERS PROFILES - Locatelli, Elisabetta; Coman, Alessandra (AoIR Selected Papers of Internet Research, 2026)
The rise of the creator economy has led mom and family influencers to integrate their children into their online narratives, enhancing their relatability and commercial value. Through emotional connection with audiences, influencers secure partnerships and build their brands. Children presence raises ethical concerns, including privacy threats, commodification of intimacy, and the pressures of algorithm-driven content production. The research investigates how family influencers negotiate the imperative to share their children and whether resistance emerges among influencers and users. The study adopts a multi-method approach employing: content analysis of Instagram and TikTok posts published by family influencers; a survey targeted mothers with at least a child aged 0-5 years; in-depth interviews with mothers and influencers. Findings reveal a constant presence of children visibility in influencers’ content with children also are actively involved in sponsored posts and stories. Opinions about children’s inclusion in visual content are mixed, with questionnaire and interviews showing that some think that it is acceptable, while other objects that risks are too high. Influencers who do not share pictures of their children acknowledge the potential sponsorship losses. The study suggests a growing awareness of digital privacy risks, where financial incentives compete with ethical considerations.